Planned maintenance management case study (Kompleks Islam Kuala Selangor, Selangor Darul Ehsan) / Nurzulaikha Mohd Arif - Mohd Arif, Nurzulaikha (Universiti Teknologi Mara, Perak, 2016)
Building maintenance work is defines as a preparation of building care that was complete and ready to residence. Building maintenance can be dividing as planned and unplanned maintenance. The planned maintenance is also can be dividing by two part that is preventive maintenance and corrective maintenance and preventive maintenance is dividing for two schedule maintenance and condition-based maintenance. The case study that I have been chosen was Kompleks Islam Kuala Selangor. This building is totally ready to build but it is still under the supervision of contractor because that have some part and works is still not get a satisfaction by building owner. This is because of the condition of this building are still not suitable to residence and open to the placement of workers or public. The building maintenance programmed for this building is available and build by Jabatan Kerja Raya Negeri Selangor (building department). This building is use a preventive maintenance and comprehensive maintenance for maintain their building for a long time.